Ethnic Conflict and Economic Cooperation in the Borderlands: Burma, Thailand, and the Karen - Siriyanun, Sirinya; Tipparat Bubpasiri, Dr. (International Journal of Engineering and Technology, 2018)
Since 1949, the Karen ethnic minority has been engaged in an armed uprising against the Burmese government, and this uprising has defined Thai-Burmese border relations. Despite its length and impact, this conflict is easily overlooked, and has been willfully ignored by Thailand, Burma, and the international community in the optimism surrounding the start of the ASEAN Economic Community. Documentary research and interviews with participants in the conflict demonstrate that the Karen, and the armed nonstate groups which represent them, maintain the ability to end any sustained cross-border cooperation between Thailand and Burma. As such, a resolution to the conflict is necessary if the ASEAN Economic Community, and the various other projects that Thailand and Burma have envisioned for the border region, is to succeed.Â Â